PENENTUAN KUALITAS MINYAK GORENG BERDASARKAN PADA NILAI ASAM LEMAK BEBAS - Siska Rusmalina (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2018)
Indonesian society consume cooking oil in high quantities. This is caused, the cooking oil used in cooking maturation process to improve the taste. The value of free fatty acids is one of parameters to determine quality of cooking oil. Values higher fatty acid in the human body can increase the levels of bad fats or called LDL ((Low Density Lipoprotein), which triggers the emergence of heart disease. This study aims to determine  the purity and quality of cooking oil in Pekalongan City.hypertension and cancer.Tests of saturated fatty acid numbers are carried out, referring to the Indonesian National Standard (SNI) 01-3741-2013. Terms of good quality oil in alkalimetry method  not more than 0.6 mgKOH / g.  The sample in this study was a sample of bulk and packaged cooking oil in the Pekalongan region.Samples obtained were 19 packaged cooking oils and 6 bulk cooking oils. The test results indicate that the fatty acids of the 25 samples tested were in the range of 0.040 to 0.5 mgKOH / g sample. Overall samples meet the required standard of SNI 01-3741-2013 that is not more than 0.6 mgKOH / g sample. so it can be concluded that the quality of cooking oil sold in the Pekalongan region is good.